On The Analysis of Received Signal Strength Indicator from ESP8266 - Shazwani Rosli, Rafhanah; Hadi Habaebi, Mohamed; Rafiqul Islam, Md (Bulletin of Electrical Engineering and Informatics, 2019)
Recently, the concept o Internet of Things has gained a tremendous momentum in the technological world. Internet of Things efficienty connects devices hence improving their quality of life from various aspects. One of the most heavily used device for Internet of Things application is ESP8266 WiFi serial transceiver module. It features access to the Received Signal Strength Indicator readings from the module. In this paper, a characteristic analysis of the Received Signal Strength Indicator readings collected using ESP8266 WiFi serial transceiver module is carried out. The aim is to explore the future possibilities of Received Signal Strength Indicator value as a stand-alone and unique parameter to be used in various applications especially in the domain of Internet of Things. In addition, the potential of the cheap yet sophisticated ESP8266 WiFi serial transceiver module is also highlighted. The findings have shown an insight into the characteristics of Received Signal Strength Indicator readings and how it can be utilized for other different purposes. The findings have brought up a few stimulating issues that may arise from some implementation of Received Signal Strength Indicator readings such as the significant effect of obstruction in the Line of Sight. However, its solution will thrust the Internet of Things’ technological advancements ahead.